A study of high-, middle- and low-molecular weight adiponectin in urine as a surrogate marker for early diabetic nephropathy using ultrasensitive immune complex transfer enzyme immunoassay. (September 2018) - Yamamoto, Mayumi; Fujimoto, Yuki; Hayashi, Shino; Hashida, Seiichi
Background: For the early identification of patients at risk of developing diabetic nephropathy, we have developed an ultrasensitive immune complex transfer enzyme immunoassay to measure adiponectin in urine. Methods: We developed immune complex transfer enzyme immunoassay for adiponectin and measured urinary adiponectin from 70 healthy subjects, 35 obese non-diabetic subjects and 20 patients with diabetes. Results: The urinary adiponectin concentrations in patients with diabetes (3.3 ± 10.7 ng/mg creatinine) were significantly higher than those in obese subjects (0.54 ± 0.44; P < 0.01) and healthy subjects (0.46 ± 0.42; P < 0.001). The gel filtration elution profile of urine from healthy subjects showed traces of four immunoreactive peaks (high-, medium-, low-molecular weight and monomer molecules), despite the majority of blood adiponectin being high-molecular weight. However, urinary adiponectin molecules were more frequent in low-molecular weight as the estimate glomerular filtration rate decreased. Furthermore, as blood glucose concentrations rose, middle-molecular weight and high-molecular weight increased in urine. Further, urinary adiponectin concentrations correlated with estimate glomerular filtration rate ( r = −0.61, P < 0.001), but not urinary albumin. In addition, our analysis showed a significantly ( P < 0.001) higher value for urinary adiponectin in the G2 stage of chronic kidney disease classification where urinary albumin is not elevated. Conclusion: Adiponectin increases in urine as renal function decreases, and urinary adiponectin may be useful as a surrogate marker for diabetic nephropathy risk.